Prevalence of co-existing autoimmune and autoinflammatory diseases in vitiligo: a survey-based study from Egypt - Samar Tharwat; Fatma Hamdy; Sara Hamdy; Mohammed Kamal Nassar (BMC Rheumatology)
Abstract Background The exact cause of vitiligo is still unknown. Genetic factors, self-destruction of melanocytes, the autoimmune process, and oxidative stress all can contribute to the pathogenesis of vitiligo. Objectives The aim of this study was to figure out the frequency of coexisting autoimmune and autoinflammatory diseases (AIIDs) in Egyptian patients with vitiligo and identify the associated risk factors. Materials and methods Egyptian children and adults with vitiligo and their parents were asked to answer a web-based survey. The survey consisted of multiple questions centered around demographic, clinical, and therapeutic data. The vitiligo disease activity (VIDA) score was evaluated for all the patients. Patients were also asked about the presence of co-existing AIIDs. Results There was a total of 294 participants, mostly females (54.8%), with a median age of 35 years and a median disease duration of 9 years. Nearly 27% had at least one AIID. The most common associated AIIDs were autoimmune thyroid disease (47 patients, 16%), followed by alopecia areata (14 patients,4.8%), then psoriasis and rheumatoid arthritis (11 patients, 3.7%). Univariate regression analysis revealed that age (OR 1.02, P = 0.036), female gender (OR 2.2, P = 0.004), disease duration (OR 1.04, P < 0.001), affected body surface area (OR 1.7, P = 0.048), and family history of AIIDs (OR 2.7, P < 0.001) were predictors for the presence of AIIDs in patients with vitiligo. Conclusion AIIDs are prevalent among vitiligo patients. Age, female gender, and family history of AIIDs are the main predictors of the presence of AIIDs in vitiligo patients.